Accuracy of commercial systems for identification of Burkholderia pseudomallei versus Burkholderia cepacia. - Kiratisin, P; Santanirand, P; Chantratita, N; Kaewdaeng, S (2007)
Infection caused by Burkholderia pseudomallei or Burkholderia cepacia may result in fatal outcome unless the causative agent is accurately identified in a short period, which is critical for treatment. We evaluated the reliability of the commonly used commercial systems, API 20NE, VITEK 2, and WalkAway 96, for comparative identification of B. pseudomallei versus B. cepacia clinical isolates. Based on biochemical and molecular tests as reference methods, API 20NE was probably the most reliable, with an accuracy of 87% and 93%, for the identification of B. pseudomallei and B. cepacia, respectively. The VITEK 2 and WalkAway 96 systems resulted in a number of misidentification and, thus, were less reliable. The performance of each system and identification guidelines for B. pseudomallei and B. cepacia are discussed. Our study emphasized that laboratories should carefully interpret the identification of B. pseudomallei and B. cepacia when using commercial systems.